PENGARUH SENAM LANSIA TERHADAP PENURUNAN TINGKAT RESIKO JATUH DI PANTI WERDHA MELANIA JAKARTA TAHUN - Cindy Phatikasari (STIKes IMC Bintaro, 2017)
In the elderly there is a physiological decline in the musculoskeletal system, the decrease in the number and size of muscle fibers, resulting in decreased lower extremity muscle strength, resistance, coordination and limited range of motion (ROM) causing impaired balance causing falls in the elderly. For that purpose, a study aimed to determine the effect of laughter therapy on the decreased risk of falling in the elderly at Panti Werdha Melania Jakarta. This study uses Quasi Experimental with one group pretest post-test design. The instrument used is the Timed Up and Go Test scale (TUGT). Technique of taking data by purposive sampling method. The population in this study is elderly Panti Werdha Melania Jakarta who meet inclusion criteria for 3 weeks. With the result of the average risk score fall before the advanced gymnastics is 2.10 and the average result after the elderly gymnastics is 1.93.